Effect of Recruitment and Placement on Employee Performance at PT. Revelation of Septyan Bengkulu - Ripi Pitriyanti; Oni Yulianti; Nia Indriasari (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the effect of recruitment and job placement on employee performance at PT. Wahyu Septyan Bengkulu. The sample in this study were 84 outsourced employees at PT. Wahyu Septyan Bengkulu. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression indicate that there is a positive influence between recruitment and placement on employee performance at PT. Wahyu Septyan Bengkulu because the direction of the regression has a positive direction, namely Y = 10,471+ 0,316X1 + 0,305X2 + e. Recruitment has a significant effect on employee performance at PT. Wahyu Septyan Bengkulu, because the significant value of 0.000 is smaller than 0.05. This means that the increasing attention to recruitment will increase the performance of employees of PT. Wahyu Septyan Bengkulu. This illustrates that with good recruitment between employees and leaders and between employees and other employees, performance can be improved. Placement has a significant effect on employee performance at PT. Wahyu Septyan Bengkulu because the significant value of 0.002 is smaller than 0.05. This illustrates that the more precise the placement of employees, the performance will also increase. Recruitment and placement have a significant effect together on employee performance at PT. Wahyu Septyan Bengkulu, thus the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant influence between recruitment and placement on performance together. The coefficient of determination of R square is 0.304. This means that recruitment and placement affect performance by 30.4% while the rest (100-30.4% = 43.3%) is influenced by other causal factors not examined in this study.